Pelatihan Pencatatan dan Pelaporan Kasus Kekerasan Terhadap Perempuan dan Anak di Wilayah Hukum Kabupaten Buton - Samsul Samsul; La Gurusi; Waode Novita Ayu Muthmainna; Eko Satria; L.M Ricard Zeldi Putra; Al Hiday Nur; La Asiri (Journal of Community Development, 2025)
The numerous legal instruments and various agencies involved in the protection of women and children have not led to a reduction in violence against women and children; rather, the incidence has been increasing annually. The primary reasons for the rise in violence against women and children are the lack of education and awareness regarding human rights, gender equality, and gender-based violence, as well as the insufficient support from communities or social networks closest to the victims. This can result in victims feeling isolated and without a place to report or seek help. The method used in this community service program was training on case recording and reporting of violence against women and children. The result of the training was an increase in participants' knowledge regarding the forms of violence against women and children, the roles and duties of the Village Task Force for the Protection of Women and Children (PPA), as well as the procedure for handling cases of violence against women and children. The success of this program was measured using questionnaires administered before and after the training to assess the participants' knowledge and understanding of case recording and reporting of violence against women and children.